Protective Effect of Edaravone Against AÎ²25-35-Induced Mitochondrial Oxidative Damage in SH-SY5Y Cells - Zhang, G-L.; Zhang, L.; Guo, Y-Y.; Ma, Z-L.; Wang, H-Y.; Li, T.; Liu, J.; Du, Y.; Yao, L.; Li, T-T.; Du, J-M. (Cellular and Molecular Biology, 2017)
Amyloid-Î² (AÎ²)-induced oxidative stress plays an important role in the pathogenesis of Alzheimer’s disease (AD). Recent studies show that AÎ² accumulation may lead to mitochondrial oxidative damage. In the present study, we investigated the protective effect of edaravone on mitochondrial damage in SH-SY5Y cells treated with AÎ²25-35. SH-SY5Y cells were pre-treated with 20, 40 or 80 Î¼M edaravone before treatment with 25 Î¼M AÎ²25-35. After 24h cell culture, cellular apoptosis, intracellular reactive oxygen species (ROS), mitochondrial membrane potential (Î”Î¨m), ATP levels and mitochondrial morphology were evaluated. SH-SY5Y cells exposed to AÎ²25-35 had high levels of apoptosis and ROS; loss of Î”Î¨m, decreased ATP levels and presence of mitochondrial swelling. However, these effects were significantly inhibited by edaravone pre-treatment. These results indicate that edaravone prevents mitochondria oxidative damage caused by AÎ² in SH-SY5Y cells, which suggests that it may have potential clinical application in AD therapy.